Mathematical Model with Pressure Constraints to Minimize Electric Energy Costs in the Operation of Hydraulic Pumps - Miquelin, Leticia Maria [UNESP]; Santos, Maristela Oliveira Dos; Mansano Furlan, Marcos; Soler, Edilaine Martins [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Water supply systems are responsible for providing quality water to the population in sufficient quantity. As sanitation companies are major energy consumers of electrical power, they have a contract of power in which the cost of electricity varies according to the period of the day. Thus, for these companies, at peak times the price of electricity is much higher. Most of the expenditure on electricity in water supply systems is due to hydraulic pumps, which are activated when the level of the tanks reaches the minimum level and remain on until the maximum levels are reached, without taking into account the time where this operation is performed. This work proposes a mathematical model for the optimization of electricity costs in water supply systems through the planning of the operation of hydraulic pumps. Numerical tests were performed through the implementation of the proposed model in GAMS software and solved by the CPLEX optimization package for different demand scenarios, in order to validate the proposed model. A model that simulates the operation performed in the practice of water supply systems is also presented, and its results are compared to the proposed optimization model. The obtained results proof of the efficiency of hydraulic pumps operation planning provided by the proposed model in relation to the operation performed in practice in water supply systems.
Keywords: Electricity; hydraulic pumps; optimization; water supply systems